Cryoresistance of Organotypic Cultures Derived from Adrenal Tissues of Rats of Various Ages - Bondarenko, T. P.; Rumiekh, Yu. Kh. (Problems of Cryobiology and Cryomedicine, 2007)
The paper covers the studies in cryosensitivity of organotypic cultures derived from the adrenal tissues of white rats of various ages (1, 3, 6, 12 and 24 months ) based on the analysis of viable cells in culture prior to and after cryopreservation in 5% dimethyl sulfoxide presence. It has been established that secreting ability of culture cells depends on an age of the animal that the tissues were derived from. The cultures of tissues of aged animals (12-24 months) have lower activity and higher sensitivity to low temperature effect.